Health risk assessment for exposure to nitrate in drinking water from village wells in Semarang, Indonesia. (September 2016) - Sadler, Ross; Maetam, Brooke; Edokpolo, Benjamin; Connell, Des; Yu, Jimmy; Stewart, Donald; Park, M.-J.; Gray, Darren; Laksono, Budi
Abstract: The levels of nitrate in 52 drinking water wells in rural Central Java, Indonesia were evaluated in April 2014, and the results were used for a health risk assessment for the local populations by using probabilistic techniques. The concentrations of nitrate in drinking water had a range of 0.01–84 mg/L, a mean of 20 mg/L and a medium of 14 mg/L. Only two of the 52 samples exceeded the WHO guideline values of 50 mg/L for infant methaemoglobinaemia. The hazard quotient values as evaluated against the WHO guideline value at the 50 and 95 percentile points were HQ50 at 0.42 and HQ95 at 1.2, respectively. These indicated a low risk of infant methaemoglobinaemia for the whole population, but some risk for the sensitive portion of the population. The HQ50 and HQ95 values based on WHO acceptable daily intake dose for adult male and female were 0.35 and 1.0, respectively, indicating a generally a low level of risk. A risk characterisation linking birth defects to nitrate levels in water consumed during the first three months of pregnancy resulted in a HQ50/50 values of 1.5 and a HQ95/5 value of 65. These HQ values indicated an elevated risk for birth defects, in particular for the more sensitive population. A sanitation improvement program in the study area had a positive effect in reducing nitrate levels in wells and the corresponding risk for public health. For example, the birth defect HQ50/50 values for a subset of wells surveyed in both 2014 and 2015 was reduced from 1.1 to 0.71. Abstract : Probabilistic risk assessment was used to predict health effects of nitrate in Indonesia groundwaters and demonstrates the potential of improved sanitation to reduce the incidence of associated health effects.